Taṭwīr Kitāb al-‘Arabiyyah bi al-Mu‘jam al-Muṣawwar (Dirāsah al-Baḥts wa al-Taṭwīr bi MTsN 4 Banda Aceh, Indonesia) - Putri Mauliana; Mukhlisah Mukhlisah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The researchers found that students could not understand the text well due to lack of vocabulary and lack of variety in color, and the way tables are presented. Consequently, students found it difficult and unmotivated to learn Arabic. For this reason, the researchers want to develop a book with a pictorial dictionary. This study aimed to determine the validity and ability to develop a book with a pictorial dictionary. This research uses the R&D (Research and Development) method, including direct observation, questionnaires, and tests as the research instruments. Researchers took 30 students of class IX-1 as the sample. The researcher used the T-test formula from the SPSS program and an expert assessment questionnaire for the data analysis. Furthermore, the study found that the development of the Pictorial Dictionary is valid according to expert assessment at 80.89% and 91.7%. Also, the results obtained were that pictorial dictionaries effectively improved students' abilities in understanding words (mufradat) and Arabic texts. Based on the results of the value of Sig. 0.00 <0.05. This result shows that Ho was rejected and Ha was accepted.